9 Association between pulse wave velocity and measures of cardiac function in healthy individuals. (21st November 2022) - Russell, Sophie L; Rahman, Mushidur; Okwose, Nduka C; Steward, Charles J; Harwood, Amy E; McGregor, Gordon; Raleigh, Stuart; Sandhu, Hardip; Roden, Laura; Banerjee, Prithwish; Jakovljevic, Djordje G
Abstract : Background: Pulse wave velocity (PWV), a measure of arterial stiffness and function, is an important cardiovascular risk factor. However, there is limited evidence reporting the association between arterial stiffness and cardiac function. Aim: Evaluate the relationship between PWV and echocardiography measures of cardiac function. Methods: Forty healthy participants (age 33±10 years, 17 females) underwent resting PWV assessment using carotid-femoral artery tonometry in the supine position, and transthoracic echocardiography for evaluation of diastolic function (left ventricular (LV) stiffness index, E to early diastolic mitral annular tissue velocity (E:e'), early to late diastolic transmitral flow velocity (E/A ratio), early diastolic myocardial tissue velocity (lateral E') and late ventricular filling (MV A)) and left ventricular systolic function (left ventricular ejection fraction (LVEF), stroke volume (SV) and left ventricular global longitudinal strain (LVGLS)). Results: The mean values of the selected variables were: PWV 6.2±0.91 ms -1, diastolic function (LV stiffness index, 0.04±0.01 ml -1 ; E:e', 4.30±1.07; MV E/A ratio, 1.51±0.30; lateral E', 0.15±0.03 ms -1 ; MV A wave, 0.46±0.08 ms -1 ) and systolic function (LVEF, 60.6±3.32%; SV, 71.3±14.5 mL and LVGLS -19.2±1.3%). A significant relationship was seen between PWV and diastolic function (LV stiffness index, r =0.36, p =0.02; E:e' r =0.32, p =0.04; E/A ratio r =-0.53, p <0.01; lateral E' r =-0.49, p <0.01 and MV A wave r =0.34, p =0.03). There was no significant relationship between PWV and systolic function (LVEF r =-0.18, p =0.26; SV, r =-0.22, p =0.17 and LVGLS r =0.16, p =0.33). Conclusion: A significant relationship between pulse wave velocity and measures of diastolic function suggests that arterial stiffness may influence diastolic function in young, healthy individuals.